Model Model of Resolving Student’s Difficulties in Understanding Recount Text : A Single Case Study of Second Grade Student at SMP Negeri 4 Blitar - Rosyada, Wildani; Supriyono, Supriyono; Primasari, Yusniarsi; Fauzi, Adin (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
This research aims to identify the challenges students face in understanding recount texts, describe the methods teachers use to address these issues, analyze student-teacher interactions in the classroom, and assess the effectiveness of the strategies implemented to enhance student comprehension. Using a qualitative approach and a single case study method, the research involved teachers, school principals, and eighth-grade students. Data were collected through observations, interviews, and documentation. The findings reveal that eighth-grade students encounter several difficulties in understanding recount texts, including challenges with unfamiliar vocabulary, long sentences separated by commas, text structure, and words with affixes. Specifically, students struggle with new vocabulary, lengthy sentences that hinder comprehension, and the organization of events in the text. To address these issues, teachers employ various strategies. For vocabulary difficulties, students are encouraged to repeatedly read the text and look up unfamiliar words in the dictionary. To tackle long sentences separated by commas, they are taught to break the sentences into shorter parts, interpret each segment, and understand its context within the story. For text structure, the teacher provides detailed explanations, and for words with affixes, relevant examples of prefixes and suffixes are given. These strategies help create a positive and active classroom environment, contributing to improved student understanding of the material. The research demonstrates that the teacher's methods effectively enhance students' comprehension of recount texts. Keyword : Difficulties, Recount Text, Strategy, Model